The people of the book - Khan, Saniyasnain; Gurmeet (Goodword Kidz New Delhi, 2004)
"The People of the Book" is a novel by Geraldine Brooks that explores the historical and spiritual journey of a Jewish manuscript known as the Sarajevo Haggadah. The story unfolds through multiple timelines, focusing on the lives of various characters who are connected to the manuscript, including a Jewish scribe in 15th-century Spain, a Muslim librarian in World War II-era Sarajevo, and an Australian rare book conservator in the present day. As the narrative weaves through themes of faith, survival, and cultural heritage, the novel highlights the resilience of the Jewish people and the shared history of the Abrahamic faiths, underscoring the enduring power of art and literature in bridging divides.